Positive electrode sheet for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

By controlling the relationship between the specific surface area and content of conductive additives in the positive electrode active material layer, and combining positive electrode active materials with specific electronic conductivity, the problem of poor electronic conductivity in non-aqueous electrolyte secondary batteries has been solved, achieving high capacity and high output characteristics, while improving manufacturing adaptability and battery performance.

CN120858464APending Publication Date: 2025-10-28FUJIFILM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202480017582.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-28
Filing Date
2024-03-27
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In the manufacturing process of non-aqueous electrolyte secondary batteries, the poor electronic conductivity of the positive electrode active material layer leads to poor battery performance, especially in terms of high capacity and high output characteristics. Furthermore, it is difficult to simultaneously achieve the dispersion stability and coating adaptability of the slurry.

Method used

By controlling the specific surface area and content of the conductive aid in the positive electrode active material layer so as to satisfy a specific relationship, and combining the positive electrode active material with an electronic conductivity within a specific range, a positive electrode sheet with a thickness of more than 120 μm is formed to ensure electronic conductivity and dispersion stability. The conductive aid with a specific specific surface area and its content in the positive electrode active material layer satisfy 5≤x×y≤420, and the electronic conductivity z is greater than 1.0.

Benefits of technology

This technology achieves high capacity and high output characteristics in non-aqueous electrolyte secondary batteries, while improving manufacturing adaptability and battery performance, and ensuring the smoothness and electronic conductivity of the positive electrode active material layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120858464A_ABST
    Figure CN120858464A_ABST
Patent Text Reader

Abstract

A positive electrode sheet in which a positive electrode current collector and a positive electrode active material layer are laminated, said positive electrode sheet being characterized in that: the positive electrode active material layer contains a positive electrode active material and a conductive auxiliary agent and has a thickness of 120 [mu] m or more; the specific surface area x (m2 / g) of the conductive auxiliary agent and the content y (mass%) of the conductive auxiliary agent in the positive electrode active material layer satisfy 5 < = x * y < = 420 and satisfy 100 < = x, and the electron conductivity z (mS / cm) of the positive electrode active material is 1.0 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a positive electrode sheet for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery obtained by using the positive electrode sheet for the non-aqueous electrolyte secondary battery. Background Technology

[0002] Non-aqueous electrolyte secondary batteries, represented by lithium-ion batteries, possess high energy density and excellent storage performance and low-temperature operation, making them widely used in portable electronic devices such as mobile phones and laptops. Furthermore, these batteries can be scaled up for use in transportation equipment, primarily automobiles, and are also used as storage devices for nighttime power and electricity generated from natural energy sources.

[0003] A general manufacturing method for a non-aqueous electrolyte secondary battery is described. First, a positive electrode sheet consisting of a laminated structure of a positive electrode current collector and a positive electrode active material layer, and a negative electrode sheet consisting of a laminated structure of a negative electrode current collector and a negative electrode active material layer, are arranged facing each other with a separator sandwiched between the positive and negative electrode active material layers, thus obtaining an electrode laminate. Typically, this electrode laminate is further wound to obtain a wound electrode body, which is then stored in a battery casing or similar container. Next, an electrolyte is poured into the battery casing, allowing it to permeate the entire positive electrode active material layer, the separator, and the negative electrode active material layer. Then, by charging and discharging (initializing) the obtained battery, an SEI (Solid Electrolyte Interface) film is formed on the negative electrode, thus obtaining a non-aqueous electrolyte secondary battery.

[0004] Among electrode active materials, carbon-based materials are widely used as negative electrode active materials due to their high electronic conductivity. On the other hand, the electronic conductivity of positive electrode active materials is generally lower than that of carbon-based materials. Therefore, improving the electronic conductivity of the positive electrode active material in non-aqueous electrolyte secondary batteries is considered a crucial technical requirement for improving battery output characteristics. A technique for improving battery performance by modifying the positive electrode active material is proposed. For example, Patent Document 1 describes an invention for a non-aqueous electrolyte energy storage element, comprising: a positive electrode, in which a positive electrode active material contains a lithium transition metal compound with a carbon-coated multi-anionic structure, and substantially does not contain a conductive agent; and a non-aqueous electrolyte with a viscosity of less than 4.2 mPa·s at 25°C. According to the technique described in Patent Document 1, a non-aqueous electrolyte energy storage element with excellent low-temperature discharge characteristics after high-temperature storage can be provided.

[0005] Previous technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-139794 Summary of the Invention

[0008] The technical problem to be solved by the invention

[0009] In the manufacture of non-aqueous electrolyte secondary batteries, the positive electrode active material layer is typically formed by coating a slurry containing the positive electrode active material and conductive additives (positive electrode forming slurry) onto the positive electrode current collector and then drying it. To improve manufacturing efficiency, the characteristics of the positive electrode forming slurry need to be controlled from various angles. For example, to improve the operability of the positive electrode forming slurry and to form the positive electrode active material layer uniformly and with high precision, the slurry must exhibit an appropriate low viscosity and be able to maintain a stable dispersion state (dispersion stability) of the solid particles (positive electrode active material and conductive additives) it contains. Furthermore, to shorten the time required, the positive electrode forming slurry must be able to dry quickly after coating (drying ease).

[0010] From the perspective of easy drying, it is advisable to reduce the amount of solvent in the cathode forming slurry and to use a slurry with a higher concentration of solid components (the total amount of active material and conductive additives). However, if the concentration of solid components in the cathode slurry increases, the viscosity of the slurry increases, and agglomeration is more likely to occur, resulting in reduced dispersion stability and poorer coating adaptability. As a result, the uniformity of the obtained cathode active material layer is compromised, and the surface becomes rough, which can easily lead to performance deviations between the resulting batteries.

[0011] Furthermore, in order to achieve high capacity (high energy density) in non-aqueous electrolyte secondary batteries, attempts were made to include a higher content of storage ions in the positive electrode active material layer, while conversely suppressing the content of conductive additives. However, if the positive electrode active material layer is made thicker to increase the amount of positive electrode active material, its thickness will hinder the efficient movement of electrons within the positive electrode active material layer. In addition, suppressing the content of conductive additives will further reduce electron conductivity, which will become unfavorable in output characteristics. Attempts were made to balance high capacity and high output characteristics by using a small amount of conductive additives with a high specific surface area that are easy to construct an electron conduction network, but conductive additives with a high specific surface area cause the aggregation of solid particles in the slurry, making it more difficult to ensure dispersion stability.

[0012] The objective of this invention is to provide a positive electrode sheet for a non-aqueous electrolyte secondary battery that exhibits excellent manufacturing adaptability and superior battery performance. Furthermore, the objective of this invention is to provide a non-aqueous electrolyte secondary battery obtained using this positive electrode sheet.

[0013] Based on repeated and in-depth research into the aforementioned issues, the inventors discovered the following: When using a positive electrode active material that controls electron conductivity within a specific range, and when the conductive additive in the positive electrode active material layer has a specific surface area exceeding a certain value, and when this specific surface area and the content of the conductive additive in the positive electrode active material layer (in the solid component of the slurry for forming the positive electrode active material) satisfy a specific relationship, even if the positive electrode active material layer is relatively thick, a positive electrode active material layer with excellent smoothness and significantly improved electron conductivity can be formed. This allows for a higher level of achievement in balancing high capacity and high output characteristics in the obtained non-aqueous electrolyte secondary battery. This invention was completed based on further repeated research using these insights.

[0014] means for solving technical problems

[0015] The aforementioned problems of the present invention have been solved by the following method.

[0016] [1]

[0017] A positive electrode sheet is formed by stacking a positive electrode current collector and a positive electrode active material layer, wherein...

[0018] The aforementioned positive electrode active material layer comprises positive electrode active material and conductive additives, and has a thickness of more than 120 μm.

[0019] The specific surface area x (m²) of the above conductive additive 2 The content y (mass%) of the above-mentioned conductive additives in the above-mentioned positive electrode active material layer satisfies 5 ≤ ​​x × y ≤ 420, and satisfies 100 ≤ x.

[0020] The electron conductivity z (mS / cm) of the above-mentioned positive electrode active material is above 1.0.

[0021] [2]

[0022] According to the positive electrode sheet described in [1], wherein,

[0023] The above x, y and z satisfy z≤(-0.0175×x×y)+10.

[0024] [3]

[0025] According to the positive electrode sheet described in [1] or [2], wherein,

[0026] The surface resistance of the above-mentioned positive electrode active material is 1.0 × 10⁻⁶. 8 Below Ω.

[0027] [4]

[0028] According to any one of [1] to [3], the positive electrode sheet, wherein,

[0029] The carbon content on the surface of the above-mentioned positive electrode active material layer is less than 5.0% by mass.

[0030] [5]

[0031] According to any one of [1] to [4], the positive electrode sheet, wherein,

[0032] In the Raman spectral analysis of the above positive electrode active material surface, the ratio of the peak intensity of the G band to the peak intensity of the D band (G / D) is 0.5 to 4.0.

[0033] [6]

[0034] According to any one of [1] to [5], the positive electrode sheet, wherein,

[0035] When the above-mentioned positive electrode sheet was heated from 25°C to 600°C at a rate of 5°C / min under a nitrogen atmosphere, the mass decreased to less than 1% by mass.

[0036] [7]

[0037] A non-aqueous electrolyte secondary battery having a positive electrode sheet as described in any one of [1] to [6] as the positive electrode.

[0038] In the description of this invention, the numerical range indicated by “~” refers to the range including the values ​​recorded before and after “~” as the lower limit and upper limit values.

[0039] In this invention, "non-aqueous electrolyte" refers to an electrolyte that is substantially free of water. That is, the "non-aqueous electrolyte" may contain trace amounts of water without impairing the effects of this invention. In this invention, the water concentration of the "non-aqueous electrolyte" is 200 ppm (by mass) or less, preferably 100 ppm or less, and more preferably 20 ppm or less. Furthermore, it is practically difficult for a non-aqueous electrolyte to be completely anhydrous; it typically contains more than 1 ppm of water.

[0040] Furthermore, in this invention, "non-aqueous solvent" also refers to a solvent that substantially does not contain water. That is, a "non-aqueous solvent" may contain trace amounts of water without impairing the effects of this invention. In this invention, the water concentration in the "non-aqueous solvent" is 200 ppm (mass basis) or less, preferably 100 ppm or less, and more preferably 20 ppm or less. In addition, it is practically difficult for a non-aqueous solvent to be completely anhydrous, and it typically contains more than 1 ppm of water.

[0041] Invention Effects

[0042] The positive electrode sheet for non-aqueous electrolyte secondary batteries of the present invention exhibits excellent manufacturing adaptability. By assembling it as the positive electrode of a non-aqueous electrolyte secondary battery, a non-aqueous electrolyte secondary battery exhibiting excellent battery performance can be obtained. The non-aqueous electrolyte secondary battery of the present invention has excellent manufacturing adaptability and also excellent battery performance. Attached Figure Description

[0043] Figure 1 This is a schematic longitudinal sectional view of a basic stacked structure of a secondary battery according to the present invention. Detailed Implementation

[0044] Preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments except as provided herein.

[0045] [Positive electrode sheet]

[0046] The positive electrode sheet of the present invention is a positive electrode sheet formed by stacking a positive electrode current collector and a positive electrode active material layer, and is a positive electrode sheet suitable for use as a positive electrode sheet in a non-aqueous electrolyte secondary battery.

[0047] In the positive electrode sheet of the present invention, the positive electrode active material layer comprises a positive electrode active material and a conductive additive, and has a thickness of 120 μm or more. Furthermore, the specific surface area x (m²) of the conductive additive is... 2 The content y (mass%) of the positive electrode active material layer and the conductive additive in the positive electrode active material layer satisfy 5≤x×y≤420 and 100≤x, and the electronic conductivity z (mS / cm) of the positive electrode active material is above 1.0.

[0048] Thus, by using a positive electrode active material with electron conductivity controlled within a specific range and a specific surface area of ​​100 m², 2 By using conductive additives with a specific surface area of ​​120 μm or more and controlling the relationship between the specific surface area and content of the conductive additives, even when using conductive additives with high specific surface areas, it is possible to produce a slurry with low viscosity and excellent coatability, and it also exhibits excellent electronic conductivity when used as an electrode. Therefore, it is possible to produce a thick film of 120 μm or more for the positive electrode active material layer. Furthermore, by assembling it as an electrode in a non-aqueous electrolyte secondary battery, the output characteristics of the obtained battery can be improved.

[0049] In this invention, the term "positive electrode sheet" refers to two methods: assembling it as a component into a non-aqueous electrolyte secondary battery (in the state of being assembled into the secondary battery), and serving as an electrode material before assembly into the non-aqueous electrolyte secondary battery. That is, the structure (area, thickness, etc.) of the positive electrode sheet can be used as a positive electrode, or processed into a structure that can be used as a positive electrode.

[0050] The positive electrode sheet of the present invention only needs to have a positive electrode current collector and a positive electrode active material layer stacked on it. Alternatively, the positive electrode active material layer can be stacked on both sides of the positive electrode current collector, or on one side of the positive electrode current collector.

[0051] The positive electrode active material layer can be composed of a single layer or multiple layers.

[0052] As needed, the positive electrode sheet may further have other layers. Examples of other layers include, for instance, a protective layer (release sheet), a coating, etc. Furthermore, in the positive electrode sheet of the present invention, the positive electrode active material layer is preferably laminated in a state of direct contact with the positive electrode current collector.

[0053] The thickness of the positive electrode active material layer is 120 μm or more, and can be set to 120–500 μm, preferably 120–300 μm, more preferably 120–250 μm, and even more preferably 150–250 μm.

[0054] The combination of the positive electrode active material and conductive additive of the present invention improves electronic conductivity, maintaining high efficiency even when the positive electrode active material layer is thickened. Therefore, by forming a thick film of the positive electrode active material layer, the load on each positive electrode active material particle can be effectively reduced, leading to a decrease in the interfacial resistance between the particles. As a result, it is believed that an improvement in battery output can be achieved.

[0055] The specific surface area x (m²) of the conductive additives constituting the positive electrode active material layer 2 The content y (mass%) of the conductive additive in the positive electrode active material layer satisfies 5≤x×y≤420, preferably 7≤x×y≤401, more preferably 9≤x×y≤300, even more preferably 9≤x×y≤280, and even more preferably 9≤x×y≤180.

[0056] The aforementioned "specific surface area x" can be measured using the BET method, as described below.

[0057] -BET Specific Surface Area Measurement Method-

[0058] After drying 0.2g of conductive additive at 120°C for 6 hours, the amount of gas adsorption was measured using a high-precision gas adsorption measuring device (manufactured by MICRO TRACK CO.,LTD., BELSORP mini (trade name)) under the following measurement conditions.

[0059] • Adsorption temperature: 77K

[0060] • Adsorbed gas: N2

[0061] • Balancing time: 100 seconds

[0062] • Purge gas: He

[0063] Furthermore, the aforementioned "content y of conductive additive in the positive electrode active material layer" refers to the content of conductive additive in the solid components constituting the positive electrode active material layer, for example, the proportion (mass %) of these contents in the total amount when the positive electrode active material layer contains binder in addition to the positive electrode active material and conductive additive.

[0064] The specific surface area x (m²) of the conductive additives constituting the positive electrode active material layer 2 / g) As long as the above relationship between x and y is satisfied, there are no particular limitations, but 100m is preferred. 2 / g or more, preferably 150m 2 / g or higher, further optimized for 180m 2 / g or more. The upper limit is not specifically limited; for example, the specific surface area x can actually be set to 1500m². 2 / g or less. The specific surface area x of the conductive additive is preferably between 100 and 1500 m². 2 The range of / g is more preferably 100–1200m. 2 The range of / g is further preferably 150–1000m. 2 The range of / g is further preferably 180–1000m. 2 The range of / g.

[0065] If the specific surface area x of the conductive additive is large, it is preferable from the viewpoint that even if the content y of the conductive additive in the positive electrode active material layer is reduced, the electronic conductivity of the positive electrode active material layer can still be improved.

[0066] The content y (mass%) of the conductive additive in the positive electrode active material layer is not particularly limited as long as the relationship between x and y described above is satisfied. Preferably, it is 0.03 to 4.00% by mass, more preferably 0.03 to 2.00% by mass, even more preferably 0.05 to 1.00% by mass, even more preferably 0.05 to 0.80% by mass, even more preferably 0.05 to 0.50% by mass, even more preferably 0.05 to 0.45% by mass, even more preferably 0.05 to 0.30% by mass, even more preferably 0.05 to 0.20% by mass, and particularly preferably 0.05 to 0.10% by mass.

[0067] The electronic conductivity z (mS / cm) of the positive electrode active material is 1.0 or higher, preferably 1.2 or higher. The upper limit is not particularly limited, but is practically 8.0 or lower. The range of electronic conductivity z can be set to 1.0 to 8.0, preferably 1.0 to 7.0, more preferably 1.2 to 6.0, even more preferably 1.2 to 5.0, even more preferably 1.2 to 4.0, even more preferably 1.2 to 3.0, and particularly preferably 1.2 to 2.5. If the electronic conductivity z of the positive electrode active material is within the above range, the electronic conductivity within the positive electrode active material layer can be sufficiently improved, while simultaneously enhancing manufacturing adaptability and the battery performance of the obtained battery.

[0068] The electronic conductivity of the positive electrode active material can be controlled by selecting the constituent materials of the positive electrode active material and by applying a surface coating layer to the positive electrode active material.

[0069] The electronic conductivity of the positive electrode active material can be measured using the methods described in the examples.

[0070] The specific surface area x of the conductive additive, the content y of the conductive additive, and the electronic conductivity z of the positive electrode active material are further preferably satisfied to satisfy z ≤ (-0.0175×x×y)+10. If this relationship is satisfied, there is a tendency to further improve manufacturing adaptability and battery performance.

[0071] The surface resistivity of the positive electrode active material (particles) is not particularly limited. For example, it can be 2.0 × 10⁻⁶. 8 Ω or less, more preferably 1.2 × 10 8 For values ​​below Ω, 1.0 × 10⁻⁶ is further preferred. 8 Below Ω. The resistor is preferably 2.0 × 10 Ω. 7 ~2.0×10 8 Ω, more preferably 3.0×10 7 ~1.2×10 8 Ω, further optimized to 3.0×10 7 ~1.0×10 8 Ω, further optimized to 3.0×10 7 ~8.0×10 7 Ω, further optimized to 3.0×10 7 ~6.0×10 7 Ω, further optimized to 3.0×10 7 ~5.0×10 7 Ω, further preferred to be 3.5×10 7 ~5.0×10 7 Ω. The lower the resistance, the higher the electronic conductivity. In this invention, it is preferable to use a positive electrode active material with improved electronic conductivity to a specific range.

[0072] The surface resistance of the positive electrode active material can be controlled by the selection of the constituent materials of the positive electrode active material and the surface coating treatment.

[0073] The resistance of the surface of the positive electrode active material can be measured using the methods described in the examples.

[0074] The amount of carbon on the surface of the positive electrode active material layer is not particularly limited, but preferably 7.0% by mass or less, more preferably 6.0% by mass or less, more preferably 5.0% by mass or less, more preferably 4.7% by mass or less, even more preferably 4.5% by mass or less, and even more preferably 4.0% by mass or less.

[0075] Here, the carbon content on the surface of the positive electrode active material layer is equivalent to the carbon content derived from the carbon-containing components contained in the positive electrode active material layer (e.g., surface coating of the positive electrode active material, conductive additives, binders, etc.). Setting the carbon content to 5.0% by mass or less suppresses the increase in slurry viscosity and tends to more easily form a smooth electrode. As a result, output characteristics can be improved.

[0076] The carbon content on the surface of the positive electrode active material layer is preferably 3.0 to 7.0% by mass, more preferably 3.0 to 6.0% by mass, even more preferably 3.0 to 5.0% by mass, even more preferably 3.0 to 4.7% by mass, even more preferably 3.0 to 4.5% by mass, even more preferably 3.0 to 4.0% by mass, and even more preferably 3.0 to 3.9% by mass.

[0077] The amount of carbon on the surface of the positive electrode active material layer can be measured using energy dispersive X-ray spectroscopy (SEM-EDX) and by the method described in the examples.

[0078] In Raman spectroscopy analysis of the surface of the positive electrode active material (particles), the ratio of the peak intensity of the G band to the peak intensity of the D band (also known as the G / D ratio) is preferably 0.5 to 4.0. The GD ratio is considered to represent the crystal state of the surface coating on the positive electrode active material. A higher GD ratio indicates higher crystallinity (fewer defects). If the GD ratio is within the above range, it is preferable from the viewpoint of being able to control the electronic conductivity z of the positive electrode active material within an appropriate range.

[0079] The preferred GD ratio is 0.5–3.5, more preferably 0.5–3.0, even more preferably 0.5–2.0, even more preferably 0.7–1.3, even more preferably 0.8–1.2, even more preferably 0.9–1.2, and even more preferably 1.0–1.2.

[0080] The GD ratio can be analyzed by Raman spectroscopy and measured using the methods described in the examples.

[0081] When the positive electrode sheet is heated from 25°C in a nitrogen atmosphere at a rate of 5°C / min, the mass reduction at 600°C is preferably less than 1% by mass. This mass reduction can be determined by the measurement method described in the examples.

[0082] The mass reduction based on the above measurements typically corresponds to the amount of binder component contained in the positive electrode active material layer of the positive electrode sheet. This is because the conductive additives are difficult to melt under the above measurement conditions.

[0083] In this invention, when the above-mentioned mass is reduced to less than 1% by mass, the increase in slurry viscosity caused by the adhesion of active substances due to the adhesive is suppressed, and the effect of the obstruction of electron conduction caused by the adhesive is reduced. As a result, the output characteristics can be improved, which is therefore preferred.

[0084] The components constituting the positive electrode sheet of the present invention will be described in more detail below.

[0085] Positive current collector

[0086] As a positive electrode current collector, it is not particularly limited and can be appropriately applied to positive electrode current collectors commonly used in secondary batteries. For example, Japanese Patent Application Publication Nos. 2016-201308, 2005-108835, 2012-185938, and International Patent Application Publication No. 2018 / 135395 can be appropriately referenced.

[0087] Aluminum and aluminum alloys are preferred as positive electrode current collectors.

[0088] <Positive Electrode Active Material Layer>

[0089] The positive electrode active material layer includes the positive electrode active material and conductive additives. In addition to the positive electrode active material and conductive additives, the positive electrode active material layer may also contain other components such as binders.

[0090] The content of positive electrode active material in the positive electrode active material layer also depends on the content y of conductive additive, but preferably 96.00 to 99.50% by mass, more preferably 96.00 to 99.40% by mass, even more preferably 98.00 to 99.30% by mass, even more preferably 98.50 to 99.20% by mass, and especially preferably 99.00 to 99.15% by mass.

[0091] (Positive electrode active material)

[0092] The positive electrode active material is preferably a material capable of reversibly inserting and releasing lithium ions. This material is not particularly limited as long as it exhibits the aforementioned electronic conductivity; it can also be a transition metal oxide, organic matter, sulfur or other elements capable of complexing with Li, or a sulfur-metal complex.

[0093] Among them, lithium-containing transition metal oxides are preferred as positive electrode active materials, and transition metal elements M are more preferred. a A transition metal oxide containing one or more elements selected from Co, Ni, Fe, Mn, Cu, and V. Furthermore, element M may also be mixed into this lithium-containing transition metal oxide. b (Elements of Group 1(Ia) and Group 2(IIa) of the periodic table, excluding lithium, and elements such as Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, or B). As a mixture, relative to transition metal element M. a The amount (100 mol%) is preferably 0-30 mol%. More preferably, it is Li / M a The substance is synthesized by mixing substances in a molar ratio of 0.3 to 2.2.

[0094] Specific examples of lithium-containing transition metal oxides include (MA) transition metal oxides with a layered rock salt structure, (MB) transition metal oxides with a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.

[0095] Specific examples of transition metal oxides (MA) with layered rock salt-type structures include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), and LiNi 0.85 Co 0.10 Al 0.05 O2 (lithium nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).

[0096] Specific examples of transition metal oxides (MB) with spinel-type structures include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8.

[0097] Examples of lithium-containing transition metal phosphate compounds (MC) include olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, iron pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate).

[0098] Examples of lithium-containing transition metal halophosphates (MD) include, for example, iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.

[0099] Examples of lithium transition metal silicate compounds (ME) include, for example, Li2FeSiO4, Li2MnSiO4 and Li2CoSiO4.

[0100] In this invention, the preferred positive electrode active material is a lithium transition metal phosphate compound (MC), and more preferably LiFePO4.

[0101] The shape of the positive electrode active material is not particularly restricted, but particulate form is preferred.

[0102] The average particle size (average particle size converted from spheres) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm, preferably 0.2 to 30 μm, more preferably 0.5 to 20 μm, and even more preferably 0.8 to 10 μm.

[0103] To produce positive electrode active materials of a specified particle size, conventional pulverizers or classifiers can be used. Positive electrode active materials obtained by calcination can also be used after being washed with water, acidic aqueous solutions, alkaline aqueous solutions, or organic solvents.

[0104] When using commercially available positive electrode active materials, the average particle size of the positive electrode active material shall be the value listed in the manufacturer's catalog.

[0105] In cases where information on the manufacturer's average particle size is unavailable, or when using synthetic cathode active materials, the average particle size (median particle size D50 in water) is obtained by dispersing the cathode active material in water and measuring it using a laser diffraction / scattering particle size distribution measurement device (e.g., Particle LA-960V2 manufactured by HORIBA, Ltd.). This also applies to the average particle size of solid particles other than the cathode active material.

[0106] The chemical formula of the compound obtained by the above calcination method can be measured by inductively coupled plasma (ICP) emission spectroscopy. As a simple method, it can be calculated based on the mass difference of the powder before and after calcination.

[0107] The surface of the positive electrode active material can also be coated with other metal oxides or carbon-based materials. These surface coatings can function as interfacial resistance stabilizing layers.

[0108] As surface coating materials, examples include metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si, or Li. Specifically, examples include spinel titanate, tantalum oxides, niobium oxides, and lithium niobate compounds, such as Li₄Ti₅O₂. 12 Li₂Ti₂O₅, LiTaO₃, LiNbO₃, LiAlO₂, Li₂ZrO₃, Li₂WO₄, Li₂TiO₃, Li₂B₄O₇, Li₃PO₄, Li₂MoO₄, Li₃BO₃, LiBO₂, Li₂CO₃, Li₂SiO₃, SiO₂, TiO₂, ZrO₂, Al₂O₃, B₂O₃, and Li₃AlF₆ are all examples of carbon-based materials. Furthermore, carbon-based materials such as C, SiC, and SiOC (carbon-doped silicon oxide) can also be used as surface coating materials.

[0109] From the viewpoint of improving the electronic conductivity to the desired level, the positive electrode active material is preferably coated with a carbon-based material. The positive electrode active material is preferably coated with carbon (C). In the presence of an additive (organic compound) as a carbon source, a carbon-based surface coating can be formed by calcining the positive electrode active material. Examples of additives include styrene-maleic anhydride copolymers, polystyrene, and polycarbonate.

[0110] Furthermore, the surface of the positive electrode active material can also be treated with sulfur or phosphorus.

[0111] In addition, the particle surface of the positive electrode active material can also be treated by activating light or active gas (plasma, etc.) before and after the above-mentioned surface coating.

[0112] The above-mentioned positive electrode active material can be used alone or in combination of two or more.

[0113] (Conductive additive)

[0114] As a conductive additive, as long as the specific surface area is 100m² 2For amounts of / g or higher, there are no particular restrictions, and known conductive additives as general conductive additives can be used. For example, natural graphite, artificial graphite, and other graphite-based materials that are electronically conductive; carbon blacks such as acetylene black, Ketjen black, and furnace black; amorphous carbon such as needle coke; carbon fibers such as vapor-grown carbon fibers or carbon nanotubes; carbonaceous materials such as graphene or fullerene; metal powders such as copper and nickel; metal fibers; and conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives can also be used.

[0115] In this invention, the conductive additive is preferably a carbonaceous material, preferably carbon black, and more preferably Ketjen black.

[0116] When using both positive electrode active material and conductive additives, among the aforementioned conductive additives, the following substances are designated as conductive additives: those that do not undergo Li insertion and release during battery charging and discharging, and do not function as active materials. Therefore, among conductive additives, those that function as active materials within the active material layer during battery charging and discharging are classified as active materials, not conductive additives. Whether a substance functions as an active material during battery charging and discharging is not determined by a single factor, but rather by its combination with the active material.

[0117] Commercially available products that serve as conductive additives include, for example, the following.

[0118] Ketjen Black: Carbon ECP (Specific surface area = 890 m²) 2 / g), carbon ECP600JD (specific surface area = 1480m²) 2 / g), Carbon ECP200L (specific surface area = 430m²) 2 / g)(all manufactured by Lion Corporation)

[0119] Carbon black: LITX300 (specific surface area = 180m²) 2 / g), LITX-HP (specific surface area = 100m²) 2 (All are manufactured by CABOT)

[0120] Carbon nanotubes (CNTs): BT1001M (specific surface area = 272 m²) 2 / g), BT1003M (specific surface area = 230m²) 2 / g)(all from LG Corporation), JENOTUBE 6A (specific surface area = 680m²) 2 / g), JENOTUBE10B (specific surface area = 230m²) 2 / g)(All are from JEIO Corporation)

[0121] One or more conductive additives can be used.

[0122] The shape of the conductive additive is not particularly limited, but particulate form is preferred.

[0123] The average particle size (average particle size converted from spheres) of the conductive additive is not particularly limited. For example, it is preferably 0.01 to 50 μm, more preferably 0.1 to 10 μm, and even more preferably 0.2 to 2.0 μm.

[0124] Conductive additives can also undergo surface treatment.

[0125] The surface treatment method is not particularly limited, but surface treatment using chemical treatment agents and atomic layer deposition (ALD) treatment are preferred.

[0126] As chemical treatment agents, organosilicon compounds (more preferably silane coupling agents) and organophosphonic acid compounds are preferred, and examples include methyltrimethoxysilane (MTMS), octadecyltrimethoxysilane, hexamethyldisilazane, tetraethoxysilane, trifluoropropyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, 3-aminopropyltriethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, trimethoxy(octyl)silane, 1H,1H,2H,2H-perfluorooctylphosphonic acid, 1-octylphosphonic acid, and perfluoropolyether triethoxysilane (KY1903 (trade name)).

[0127] In ALD processing, the deposited layers can include HfO2, SiO2, ZrO2, Ta2O5, TiO2, etc.

[0128] (Other ingredients)

[0129] Depending on the requirements, the positive electrode active material layer can contain binders, ionic liquids, thickeners, defoamers, leveling agents, dehydrating agents, antioxidants, etc. These are substances commonly used in non-aqueous electrolyte secondary batteries.

[0130] As adhesives, polyvinylidene fluoride (PVDF) and styrene-butadiene copolymer (SBR) are preferred.

[0131] The content of the binder in the positive electrode active material layer is preferably 0.10 to 3.00% by mass, more preferably 0.50 to 2.00% by mass, even more preferably 0.50 to 1.00% by mass, and particularly preferably 0.50 to 0.80% by mass.

[0132] <Preparation of positive electrode sheet>

[0133] The positive electrode sheet of the present invention can be prepared by forming the positive electrode active material layer on the aforementioned positive electrode current collector. When forming the positive electrode active material layer, a positive electrode slurry comprising the positive electrode active material, a conductive additive, and a dispersion medium is typically prepared. The positive electrode slurry may also contain other components as needed. Specifically, as a method for preparing the positive electrode sheet of the present invention, a coating film can be formed by coating the positive electrode slurry (which may be separated from other layers) onto the positive electrode current collector as a substrate, and then drying it to obtain an electrode sheet having a positive electrode active material layer (coated and dried layer) on the substrate. If necessary, the coating film may also be subjected to a pressing process.

[0134] The dispersion medium is not particularly limited. For example, it can be water or a non-aqueous solvent.

[0135] As a non-aqueous solvent, an aprotic organic solvent is preferred, and more preferably an aprotic organic solvent with 2 to 10 carbon atoms.

[0136] Examples of non-aqueous solvents include chain or cyclic carbonate compounds, lactone compounds, chain or cyclic ether compounds, ester compounds, nitrile compounds, amide compounds, oxazolidinone compounds, nitro compounds, chain or cyclic sulfone or sulfoxide compounds, and phosphate compounds.

[0137] In addition, compounds having ether bonds, carbonyl bonds, ester bonds, or carbonate bonds are preferred. These compounds may also have substituents.

[0138] Examples of non-aqueous solvents include ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, γ-butyrolactone, γ-valerolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, and ethyl... Methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate, ethyl trimethylacetate, acetonitrile, glutaronitrile, adiponitrile, methoxyacetonitrile, 3-methoxypropionitrile, N,N-dimethylformamide, N-methylpyrrolidone (NMP), N-methyloxazolidinone, N,N'-dimethylimidazolinone, nitromethane, nitrobenzene, sulfolane, trimethyl phosphate, dimethyl sulfoxide, or dimethyl sulfoxide phosphoric acid, etc. These can be used alone or in combination. Preferably, at least one is selected from the group consisting of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and γ-butyrolactone; more preferably, a combination of a high-viscosity (high dielectric constant) solvent (e.g., specific dielectric constant ε≥30) such as ethylene carbonate or propylene carbonate with a low-viscosity solvent (e.g., viscosity ≤1 mPa·s) such as dimethyl carbonate, methyl ethyl carbonate, or diethyl carbonate. By employing this combination of solvents, the dissociation of the electrolyte salt and the mobility of its ions are improved. The combination of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate is particularly preferred among the aforementioned non-aqueous solvents.

[0139] Furthermore, the non-aqueous solvents used in this invention are not limited to these.

[0140] In this invention, the dispersion medium is preferably N-methylpyrrolidone (NMP) or a mixed solvent of N-methylpyrrolidone (NMP) and dimethyl carbonate (DMC).

[0141] In the positive electrode slurry, the content of solid components (excluding the dispersion medium (solvent) in the slurry is preferably 70% by mass or more, more preferably 72% by mass or more, more preferably 74% by mass or more, and even more preferably 78% by mass or more. The content of this solid component is preferably 70-95% by mass, more preferably 70-90% by mass, even more preferably 72-87% by mass, even more preferably 74-85% by mass, and particularly preferably 78-83% by mass.

[0142] The method of coating the positive electrode slurry onto the positive electrode current collector is not particularly limited, and conventional methods can be used.

[0143] [Non-aqueous electrolyte secondary battery]

[0144] The non-aqueous electrolyte secondary battery of the present invention (hereinafter also referred to as the secondary battery of the present invention) sequentially comprises a positive electrode, a separator, and a negative electrode, and the positive electrode sheet of the present invention serves as the positive electrode. The secondary battery of the present invention is identical to a conventional non-aqueous electrolyte secondary battery, except that it has the positive electrode sheet of the present invention as the positive electrode.

[0145] The secondary battery of the present invention can be obtained by assembling the positive electrode sheet of the present invention into the positive electrode of the secondary battery.

[0146] The structure of a typical non-aqueous electrolyte secondary battery is described below.

[0147] Figure 1 This is a schematic cross-sectional view of a typical non-aqueous electrolyte secondary battery 10, including the working part 6 when the battery is in operation. The non-aqueous electrolyte secondary battery 10 has a stacked structure (hereinafter also referred to as an electrode stack) having, when viewed from the negative electrode side, a negative electrode current collector 1, a negative electrode active material layer 2, a separator 3, a positive electrode active material layer 4, and a positive electrode current collector 5 in sequence. The space between the negative electrode active material layer 2 and the positive electrode active material layer 4 is filled with a non-aqueous electrolyte (not shown) and separated by the separator 3. The separator 3 has pores and functions as a separation membrane between the positive and negative electrodes, allowing the electrolyte and ions to pass through while insulating the positive and negative electrodes during normal battery operation. With this structure, for example, in lithium-ion secondary batteries, electrons (electrons) are supplied to the negative electrode side via an external circuit during charging. - At the same time, lithium ions (Li) + Lithium ions (Li₂) migrate from the positive electrode to the negative electrode via the electrolyte and accumulate in the negative electrode. On the other hand, during discharge, the lithium ions (Li₂) accumulated in the negative electrode... + The electrolyte returns to the positive electrode side and supplies electrons to the working part 6. In the illustrated example, a light bulb is used in the working part 6 and is lit by discharging.

[0148] The secondary battery of the present invention replaces the positive electrode active material layer 4 and the positive electrode current collector 5 in the above-mentioned general non-aqueous electrolyte secondary battery, and has the positive electrode sheet of the present invention.

[0149] The secondary battery of the present invention, besides having the positive electrode sheet of the present invention as the positive electrode, is not particularly limited in its other components such as the negative electrode active material layer, negative electrode current collector, electrolyte (aqueous electrolyte, non-aqueous electrolyte) or solid electrolyte material, and separator. These materials and components can be appropriately applied to materials and components used in conventional secondary batteries. Furthermore, regarding the manufacturing method of the secondary battery of the present invention, in addition to using the positive electrode sheet of the present invention as the positive electrode, conventional methods can also be appropriately employed. For example, Japanese Patent Application Publication Nos. 2016-201308, 2005-108835, 2012-185938, and International Publication No. 2020 / 067106 can be appropriately referenced.

[0150] The secondary battery of this invention can be incorporated into electronic devices such as laptops, pen-and-paper computers, mobile computers, e-book readers, mobile phones, cordless phones, pagers, handheld terminals, portable fax machines, portable copiers, portable printers, stereo headphones, camcorders, LCD TVs, handheld vacuum cleaners, portable CD players, mini disk drives, electric shavers, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, and backup power supplies. Furthermore, as a civilian product, it can be incorporated into automobiles, electric vehicles, motors, lighting fixtures, toys, game consoles, load conditioners, clocks, flashlights, cameras, and medical devices (pacemakers, hearing aids, and shoulder massagers, etc.). In addition, it can be used in various military and aerospace applications. It can also be combined with solar cells.

[0151] The present invention will now be described in further detail with reference to embodiments. However, the present invention should not be construed as limited thereto.

[0152] Example

[0153] <Preparation of Positive Electrode Active Material>

[0154] Ten parts by weight of LFP (LiFePO4) powder (manufactured by Gelon, particle size 2.5 μm) were mixed with 90 parts by weight of water. Styrene-maleic anhydride copolymer was added as an additive according to the amounts shown in Table 1, and the mixture was stirred for 3 hours. Then, it was calcined at 700°C under a nitrogen atmosphere for 10 hours to obtain positive electrode active materials LFP1, LFP1-2, LFP2, LFP3, LFP4, and LFP5 with carbon-based materials coated on their surfaces.

[0155] NCM(LiNi) 1 / 3 Co 1 / 3 Mn 1 / 310 parts by weight of O2 powder raw material (manufactured by TOYOSHIMA MFG Co,.Ltd, NCM111 (trade name), particle size 8μm) were mixed with 90 parts by weight of water. Styrene-maleic anhydride copolymer was added as an additive according to the amounts shown in Table 1, and the mixture was stirred for 3 hours. Then, it was calcined at 700°C under a nitrogen atmosphere for 10 hours to obtain positive electrode active materials NCM1 and NCM2 with carbon-based materials coated on their surfaces.

[0156] <Measurement of the electronic conductivity of positive electrode active materials>

[0157] The electronic conductivity of each positive electrode active material obtained above was measured using the following method.

[0158] 30 mg of positive electrode active material was added to a cylindrical tube with an inner diameter of 10 mm and pressed at 10 MPa to form a pressed body of positive electrode active material (thickness: approximately 0.15 mm). Then, a stainless steel rod with a diameter of 10 mm was inserted into the openings at the top and bottom of the tube, with the end of the rod in contact with the surface of the pressed body, and a constant voltage of 10 mV was applied to perform resistance measurements. Three measurements were performed (N3), and the average value of the obtained resistance values ​​was calculated as the powder resistance (mΩ). Using the obtained powder resistance, the electronic conductivity of the positive electrode active material (mS / cm) was calculated using the following formula. In the following formula, film thickness refers to the thickness of the pressed body (cm), and area refers to the area of ​​the circular surface (one side) of the pressed body (cm²). 2 The resistance measurement used an electrochemical measuring device (VMP-300, manufactured by Bio-Logic Science Instruments).

[0159] The measurement results are shown in Table 1.

[0160] Electronic conductivity = 1 ÷ powder resistance × film thickness ÷ area

[0161] [Table 1]

[0162] Table 1

[0163]

[0164] <Preparation of Conductive Additives>

[0165] The following were prepared as conductive additives.

[0166] AB: Li-100 (trade name), acetylene black, specific surface area = 69m² 2 / g, manufactured by Denka Company Limited

[0167] ECP600JD: Carbon ECP600JD (trade name), Ketjen Black, specific surface area = 1480m² 2 / g, manufactured by Lion Corporation

[0168] LITX300: LITX300 (trade name), carbon black, specific surface area = 180m² 2 / g, manufactured by CABOT

[0169] Carbon ECP: Carbon ECP (trade name), Ketjen Black, specific surface area = 890 m² 2 / g, manufactured by Lion Corporation

[0170] <Preparation of positive electrode sheet>

[0171] In the positive electrode active material, conductive additive and binder, and dispersion medium listed in Table 2, the positive electrode active material, conductive additive and binder were mixed in the proportions listed in Table 2, and the dispersion medium was mixed in such a way that the solid content was 80% by mass, thereby preparing various positive electrode slurries. Polyvinylidene fluoride (PVDF) was used as the binder, and N-methylpyrrolidone (NMP) was used as the dispersion medium.

[0172] The aforementioned positive electrode slurry was coated onto one entire surface of a 12 μm thick positive electrode current collector (aluminum foil) (vertical: 300 mm, horizontal: 200 mm), and dried at 120°C until the dispersion medium was completely evaporated. Then, a pressing process was performed using a roller press to obtain a sheet-like positive electrode (positive electrode sheet) having a positive electrode current collector and a positive electrode active material layer. The thickness of the positive electrode active material layer for each positive electrode sheet was adjusted as shown in Table 2. Positive electrode sheets for Experiments No. 1 to 38 were thus prepared.

[0173] <Surface resistance of positive electrode active material (particles)>

[0174] As an indicator of the electronic conductivity of the positive electrode active material particle surface, the resistance of the positive electrode active material particle surface was measured using atomic force microscopy (AFM) as follows.

[0175] Ten mg of positive electrode active material particles were adhered to a carbon ribbon and placed on the sample stage of a scanning probe microscope (PeakForce TUNA, trade name, manufactured by Bruker). The cantilever of the microscope was brought close to the positive electrode active material particles, and the current value I (in nA) flowing through the sample was measured when a voltage was applied in microcurrent measurement mode. The voltage was applied from -1.5V to +1.5V in 0.1V increments. Thus, data for the current value I relative to the voltage value V were obtained at 31 points. The resistance value R (Ω) was obtained by linearly fitting the obtained voltage value V and current value I (as shown in the following formula) as the slope.

[0176] ·V=RI (formula)

[0177] <Carbon content on the surface of the positive electrode active material layer>

[0178] Each positive electrode sheet obtained above was punched with a diameter of 10 mm. A field emission scanning electron microscope (FE-SEM) (manufactured by JEOL Ltd., JSM7100F, trade name) was used to observe the surface of the positive electrode active material layer (the side opposite to the positive electrode current collector) at an accelerating voltage of 1.5 kV. Elemental analysis was performed using an energy dispersive X-ray spectroscope (EDX) (manufactured by Thermo Fisher Scientific Inc., Noran System 7, trade name) via automated detection. The mass ratio of carbon content detected by automated detection to the total elemental content was defined as the C content (mass%) of the positive electrode active material layer surface.

[0179] <GD ratio on the surface of positive electrode active material (particles)>

[0180] The 10 mg positive electrode active material particles obtained above were adhered to a carbon ribbon, and Raman spectra were obtained by irradiating the ribbon with a 532 nm laser using a confocal Raman microscope (manufactured by Renishaw, inVia Qontor). The G band (wavenumber 1600 cm⁻¹) of the Raman spectrum was measured at 10 points. -1 The peak intensity of ) and D band (wavenumber 1350cm) -1 The ratio of the peak intensities of the peaks is used as the average value of the G / D ratio.

[0181] In the examples, the GD ratios of the positive electrode active materials LFP1-2, LFP2-5 and NCM2 all fall between 0.7 and 1.4.

[0182] <Mass reduction of the positive electrode active material layer>

[0183] Thermogravimetry-differential thermal analysis (TG-DTA) was performed under a nitrogen atmosphere, starting at 25°C and increasing at a rate of 5°C / min. After reaching 600°C, the mass loss after standing at 600°C for 1 hour was measured. More specifically, the measurements were performed as follows.

[0184] Five mg of the sample obtained by stripping the positive electrode active material layer from the current collector was placed in the sample tray of a thermogravimetric-differential thermal analyzer (manufactured by SHIMADZU CORPORATION, TGA-50H (trade name)) and placed inside the device. The mass was measured under the following conditions.

[0185] • Gas flow rate: Nitrogen 50 ml / min.

[0186] Measurement conditions: After standing at 25°C for 2 hours, the temperature was increased to 600°C in a nitrogen atmosphere at a rate of 5°C / min, and then stood at 600°C for 1 hour.

[0187] The mass reduction was calculated using the following formula.

[0188] Mass reduction (mass%) = [(mass after standing at 25℃ for 2 hours) - (mass after standing at 600℃ for 1 hour)] ÷ (mass after standing at 25℃ for 2 hours) × 100

[0189] <Manufacturing Adaptability Evaluation>

[0190] As an indicator of the manufacturing adaptability of positive electrode sheets, the viscosity of the slurry after the positive electrode slurry is prepared and the smoothness of the electrode surface after coating are evaluated.

[0191] 1. Methods for measuring slurry viscosity

[0192] An E-type viscometer (TV-35, manufactured by Toki Sangyo Co., Ltd.) and a standard conical rotor (1”34”×R24) were used. The sample cup was set to 25°C, and 1.1 mL of the positive electrode slurry obtained above was added. The sample cup was placed on the main body and maintained for 5 minutes until the temperature stabilized. The viscosity measured at 25 rpm was then recorded as the viscosity value. The obtained viscosity value was evaluated using the following evaluation criteria.

[0193] -Evaluation Criteria-

[0194] A: Less than 100 mPa·s

[0195] B: 100 mPa·s or higher and less than 1000 mPa·s

[0196] C: Above 1000 mPa·s and below 5000 mPa·s

[0197] D: Above 5000 mPa·s and below 20000 mPa·s

[0198] E: Above 20000 mPa·s and below 50000 mPa·s

[0199] F: Above 50000 mPa·s and below 120000 mPa·s

[0200] G: Above 120000 mPa·s

[0201] 2. Smoothness Evaluation Method

[0202] Smoothness was evaluated using the thickness of the positive electrode active material layer as an indicator. Specifically, five 10mm diameter holes were punched in the central portion of each positive electrode sheet obtained above. The thickness (μm) of the positive electrode active material layer at the center of each punched sheet was measured, and the average value (T) was calculated. C Furthermore, five 10mm diameter holes were punched at locations 2cm from the end of the positive electrode sheet. The film thickness (μm) of the positive electrode active material layer at the center of each punched sheet was measured, and the average value (T) was calculated. S ). Calculate the average deviation of the film thickness between the end and the center ((|T) C -T S |) / T C The value was calculated as ×100), and the obtained value was evaluated using the following evaluation criteria.

[0203] -Evaluation Criteria-

[0204] A: Less than 1%

[0205] B: 1% or more but less than 2%

[0206] C: 2% or more but less than 4%

[0207] D: 4% or more but less than 6%

[0208] E: 6% or more but less than 8%

[0209] F: 8% or more but less than 10%

[0210] G: 10% or more

[0211] <Evaluation Methods for Electron Conductivity of Positive Electrode Sheets>

[0212] A current collector (aluminum foil) is then superimposed on the surface of the positive electrode active material layer of each positive electrode sheet obtained above, thereby forming a current collector-positive electrode active material layer-current collector laminate. The aluminum foil is ultrasonically welded to the two current collectors of this laminate, and then sandwiched between two aluminum laminate films for heat sealing and vacuum sealing, thus creating an electronic conductivity evaluation battery. A constant voltage of 10mV was applied to the battery, and resistance measurements were performed. Three measurements were performed (N3), and the average of the obtained resistance values ​​was taken as the electrode resistance (mΩ). Using the obtained electrode resistance, the electronic conductivity of the positive electrode sheet was calculated using the following formula. In the following formula, film thickness refers to the thickness of the positive electrode sheet (including the two current collectors) (cm), and area refers to the area of ​​the positive electrode sheet (vertical: 300mm, horizontal: 200mm) (cm²). 2 The resistance measurement used an electrochemical measuring device (VMP-300, manufactured by Bio-Logic Science Instruments).

[0213] Electronic conductivity = 1 ÷ electrode resistance × film thickness ÷ area

[0214] -Evaluation Criteria-

[0215] A: Above 20mS / cm

[0216] B: Above 16ms / cm and below 20ms / cm

[0217] C: Above 12mS / cm and below 16mS / cm

[0218] D: Above 8mS / cm and below 12mS / cm

[0219] E: Above 4mS / cm and below 8mS / cm

[0220] F: Above 2mS / cm and less than 4mS / cm

[0221] G: Less than 2mS / cm

[0222] <Output Characteristic Evaluation>

[0223] A secondary battery was manufactured using the positive electrode sheets obtained above, and the output characteristics of the obtained secondary battery were tested as follows. The battery performance was evaluated based on the test results. A charge-discharge evaluation device (TOSCAT-3000 (trade name), manufactured by TOYO SYSTEM CO.,LTD.) was used as the testing machine.

[0224] (Making a Second-hand Battery)

[0225] 1) Preparation of non-aqueous electrolyte A

[0226] A non-aqueous electrolyte (non-aqueous electrolyte A) was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a mass ratio of EC:DMC:EMC = 3:4:3 with LiPF6 as a lithium salt to achieve a concentration of 1M.

[0227] 2) Preparation of the negative electrode

[0228] A negative electrode slurry was obtained by mixing negative electrode active material (artificial graphite), styrene-butadiene copolymer (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, and water in a mass ratio of negative electrode active material:SBR:CMC:water = 60:1.5:0.5:38.

[0229] The aforementioned negative electrode slurry was coated onto one side of a 12 μm thick negative electrode current collector (copper foil) and dried at 150°C until the solvent was completely evaporated. Then, a pressing process was performed using a roller press to obtain a sheet-like negative electrode (negative electrode sheet) having a negative electrode current collector and a negative electrode active material layer. The thickness of this negative electrode active material layer is approximately 180 μm.

[0230] 3) Preparation of secondary batteries

[0231] Each positive electrode sheet is stacked with the negative electrode sheet obtained above through a separator to form a laminate consisting of a positive electrode current collector, a positive electrode active material layer, a separator, a negative electrode active material layer, and a negative electrode current collector, thereby obtaining an electrode laminate. Aluminum and nickel sheets are welded to the ends of the positive and negative electrode current collectors, respectively, using ultrasonic welding. A battery assembly is fabricated by housing this electrode laminate in a laminated container. An evaluation test lithium-ion secondary battery is fabricated by injecting non-aqueous electrolyte A with the injection port open, sealing the injection port, and sealing the casing.

[0232] (Charging and discharging before the experiment)

[0233] In Experiments 1-28 and 32-38, the batteries prepared above were charged to 3.6V by constant current (CC)-constant voltage (CV) charging and discharged to 2.0V by constant current (CC) discharging under the following conditions.

[0234] CC-CV charging: Current 25mA, Upper limit voltage 3.6V, Termination current 2.5mA

[0235] CC discharge: Current value 25mA, termination voltage value 2.0V

[0236] Before the above test, after charging and discharging, a piece of aluminum laminate was cut and sealed again with a vacuum sealing machine to remove unnecessary gas generated during the charging and discharging process before the test.

[0237] In the case of NCM in Experiment Examples 29 to 31, even in either CC-CV charging or CC discharging, except that the upper limit voltage was changed to 4.2V and the termination voltage to 3.0V, the charging and discharging were performed before the test in the same manner as described above.

[0238] (Output Characteristic Evaluation)

[0239] In Experiments 1-28 and 32-38, output characteristic tests were performed on batteries after charge-discharge (after exhaust) before the aforementioned tests under the following conditions. Specifically, the baseline discharge capacity was measured by charging to 3.6V via CC-CV charging and discharging to 2.0V via CC discharging under the following conditions. Then, the output evaluation discharge capacity was measured by charging to 3.6V via CC-CV charging and discharging to 2.0V via CC discharging under the following conditions. Furthermore, the discharge capacity retention rate was calculated using the following formula and evaluated using the following evaluation criteria.

[0240] Reference discharge capacity:

[0241] CC-CV charging: Current 25mA, Upper limit voltage 3.6V, Termination current 2.5mA

[0242] CC discharge: Current value 25mA, termination voltage value 2.0V

[0243] Output evaluation of discharge capacity:

[0244] CC-CV charging: Current 25mA, Upper limit voltage 3.6V, Termination current 2.5mA

[0245] CC discharge: Current 1500mA, Termination voltage 2.0V

[0246] Discharge capacity retention rate (%) = [(Output evaluation discharge capacity) / (Reference discharge capacity)] × 100

[0247] In the case of NCM in Experiment Examples 29 to 31, the output characteristic test was conducted in the same manner as above, except that the upper limit voltage was changed to 4.2V and the termination voltage was changed to 3.0V.

[0248] -Evaluation Criteria-

[0249] A: More than 80%

[0250] B: 70% or more but less than 80%

[0251] C: 65% or more but less than 70%

[0252] D: 60% or more but less than 65%

[0253] E: 55% or more but less than 60%

[0254] F: 50% or more but less than 55%

[0255] G: Less than 50%

[0256] The results are shown in Tables 2-4.

[0257]

[0258]

[0259] (Notes in Table 2)

[0260] In the "Satisfaction of Equation A" column, it is recorded whether x, y, and z satisfy z≤(-0.0175×x×y)+10. Set the satisfied case to "TRUE" and the unsatisfied case to "FALSE".

[0261] [Table 3] Table 3

[0262]

[0263] [Table 4]

[0264] Table 4

[0265]

[0266] The positive electrode sheets in Experiments No. 1 to 9, 18, 21, 25, 26, and 29 do not meet at least one of the following conditions: the specific surface area x of the conductive additive, the content y of the conductive additive in the positive electrode active material layer being 5 ≤ x × y ≤ 420 and 100 ≤ x, the electronic conductivity z of the positive electrode active material layer being 1.0, and the thickness of the positive electrode active material layer being 120 μm or more. Specifically, in Experiments No. 1 to 9, 18, 21, and 25, the viscosity of the positive electrode slurry used to form it is 20000 mPa·s or more; furthermore, the film thickness deviation is 10% or more, and the manufacturing adaptability is poor. The film thickness deviation of the positive electrode sheet in Experiment No. 26 is 10% or more. Furthermore, in Experiments No. 1 to 9, 18, 21, 25, 26, and 29, the electronic conductivity is less than 2 mS / cm, and the conductivity is poor. The discharge capacity retention rate of secondary batteries formed using these positive electrode sheets is less than 50%.

[0267] In contrast, the positive electrode sheets of the present invention in Experiments No. 10–17, 19, 20, 22–24, 27, 28, and 30–38 all have positive electrode active material layers that satisfy all the following conditions: the specific surface area x of the conductive additive and the content y of the conductive additive in the positive electrode active material layer are 5 ≤ x × y ≤ 420 and 100 ≤ x; the electronic conductivity z of the positive electrode active material layer is 1.0; and the thickness of the positive electrode active material layer is 120 μm or more. In these positive electrode sheets, the viscosity of the positive electrode slurry used to form it is reduced, and the film thickness deviation is small. This is believed to be due to improved dispersion stability of the positive electrode slurry. These positive electrode sheets also exhibit excellent electronic conductivity, and the secondary batteries formed using these positive electrode sheets also have excellent discharge capacity retention.

[0268] If equation A is satisfied, there is a tendency to further improve manufacturing adaptability and battery performance.

[0269] The invention has been described together with its embodiments, but unless otherwise specified, the invention should not be limited to any details in the description and should be interpreted broadly without departing from the spirit and scope of the invention shown in the appended technical solutions.

[0270] This application claims priority based on Japanese Patent Application 2023-051785, filed on March 28, 2023, the contents of which are incorporated herein by reference as a part of the description herein.

[0271] Symbol Explanation

[0272] 10-Non-aqueous electrolyte secondary battery, 1-Negative electrode current collector, 2-Negative electrode active material layer, 3-Separator, 4-Positive electrode active material layer, 5-Positive electrode current collector, 6-Working part (light bulb).

Claims

1. A positive electrode sheet, which is formed by stacking a positive electrode current collector and a positive electrode active material layer, wherein, The positive electrode active material layer comprises a positive electrode active material and a conductive additive, and has a thickness of more than 120 μm. The specific surface area x (m²) of the conductive additive 2 The content y (mass%) of the positive electrode active material layer of the conductive additive and the conductive additive satisfies 5 ≤ ​​x × y ≤ 420, and 100 ≤ x. The electron conductivity z (mS / cm) of the positive electrode active material is above 1.

0.

2. The positive electrode sheet according to claim 1, wherein, The x, y, and z satisfy z ≤ (-0.0175×x×y) + 10.

3. The positive electrode sheet according to claim 2, wherein, The surface resistance of the positive electrode active material is 1.0 × 10⁻⁶. 8 Below Ω.

4. The positive electrode sheet according to claim 3, wherein, The carbon content on the surface of the positive electrode active material layer is less than 5.0% by mass.

5. The positive electrode sheet according to claim 4, wherein, In the Raman spectral analysis of the surface of the positive electrode active material, the ratio of the peak intensity of the G band to the peak intensity of the D band (G / D) is 0.5 to 4.

0.

6. The positive electrode sheet according to claim 5, wherein, When the positive electrode sheet was heated from 25°C to 600°C at a rate of 5°C / min under a nitrogen atmosphere, the mass reduction was less than 1% by mass.

7. A non-aqueous electrolyte secondary battery, comprising a positive electrode sheet as claimed in any one of claims 1 to 6 as the positive electrode.

Citation Information

Patent Citations

  • Rechargeable lithium-ion secondary battery

    JP2005108835A

  • Nonaqueous secondary battery

    JP2012185938A

  • Nonaqueous electrolyte and nonaqueous secondary battery

    JP2016201308A

  • Nonaqueous electrolyte power storage element

    JP2022139794A

  • Filament-less electron source

    JP2023051785A